ANALISIS PPN DAN BEA MASUK TERHADAP HARGA JUAL PRODUK KOLEKSI POP MART DI INDONESIA - Helena Maniku; Indah Yuli Kustianah; Shafa Kamilah Maryza; Najwa Nur Kamila (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the effect of Value Added Tax (VAT) and import duties on the selling price of collectible products, using Pop Mart in Indonesia as a case study. The research employs a descriptive qualitative approach by collecting data through direct and online surveys, as well as reviewing secondary sources such as journals, articles, and relevant tax regulations. The findings indicate that VAT and import duties influence price determination but do not significantly increase the selling price. This is due to Pop Mart Indonesia receiving bulk supplies directly from the parent company, which reduces the tax burden per unit. Products sold through official stores have more stable and affordable prices compared to those obtained through unofficial channels such as personal shopping services. Therefore, an efficient distribution structure and compliance with tax regulations enable the company to maintain competitive prices in the domestic market.